Subacute ischemic stroke rehabilitation outcomes in working-age adults: The role of aphasia in cognitive functional independence. Issue 5 (4th July 2021) - García-Rudolph, Alejandro; García-Molina, Alberto; Cegarra, Blanca; Opisso, Eloy; Saurí, Joan; Tormos, Josep María; Bernabeu, Montserrat
ABSTRACT: Background: About one-third of adult stroke patients suffer from aphasia when they are discharged from hospital. Aphasia seems to be a negative predictive factor affecting post-stroke functional recovery after rehabilitation, but this association has been scarcely addressed in previous research. Objectives: We aim to evaluate the impact of aphasia in cognitive functional outcomes in working-age first-ever ischemic stroke adults. Methods: Retrospective observational cohort study. One hundred and thirty ischemic (≤ 64 years old) adult stroke patients (43.07% with aphasia) admitted to a rehabilitation center between 2007 and 2019 were analyzed. Univariate and multivariate linear regressions were performed using state-of-the-art variables (stroke severity, gender, age) extending them with potential confounders (e.g. diabetes, medication for depression). The cognitive subtest (C-FIM) of the Functional Independence Measure (FIM) at discharge and C-FIM gain were the dependent variables. Results: Patients with aphasia (PWA) had lower C-FIM scores at admission and at discharge. No significant differences were observed in relation to C-FIM gain, C-FIM efficiency, C-FIM effectiveness and length of stay (LOS). C-FIM gain was remarkably higher though non-significant ( p = .059) in PWA. Regression analysis identifies C-FIM at admission and aphasia as significant predictors of C-FIM at discharge (R 2 = 0.72). The same variables plus taking medication for depression predicted C-FIM gain (R 2 = 0.38). Conclusions: We identified no significant differences in C-FIM outcomes (gain, efficiency and effectiveness) either in LOS between PWA and patients without aphasia, though C-FIM differences were significant at admission and discharge. Aphasia was a significant predictor of C-FIM gain and C-FIM at discharge.